PENGARUH LOGOTERAPI MEDICAL MINISTRY TERHADAP DEPRESI DAN KUALITAS HIDUP PASIEN PASCA STROKE - Imron, Sri Wahyuni; Sudiyanto, Aris; Fanani, Mohammad (Biomedika, 2019)
Post-stroke depression (PSD) is the depression following stroke. It is the most frequently complication that has been occurring in stroke and impacting on functional impairment, Activity Daily Living (ADL) decreasement, cognitive deficiency, recovery inhibition, mortality increasement, motor function impairment, and progressive mobility decreasement, thereby increasing dependency and social integration disorder, giving the patients and their family difficulty, and decreasing their quality of life. Stroke is the third leading cause of death in the world with PSD prevalence rate of 5%-63%. The management of post-stroke depression should be comprehensive, managing both stroke and depression, including its risk factor. The aims of this research is to find out the effect of Medical Ministry Logotherapy on depression and quality of life post-stroke patients. This research was an analytical experimental research with single blinded randomized controlled trial pre and post-test design. The subject of research was post-stroke patients with depression in Neurological Polyclinic X Hospital of Surakarta fulfilling the restrictive criteria. The research was conducted from December to 2017 to April 2018. The sampling technique employed was simple random sampling. The instruments used were HDRS and WHOQOL. The data collected would be processed and analyzed using software. Data of general characteristics include gender, religion, education, job status, DM, duration of illness, HT with analize of Chi-Square test showed homogeneous between treatment and control, with p> 0.05. In statistic test, the change of pretes – postest score of HDRS and WHOQOL, in treatment compared with those in control groups obtained p value < 0.01, so that there was a significant difference between treatment and control groups, the decrease in HDRS and the increase in WHOQOL score. The conclusion of this study are the Logoterapi Medical Ministry is reduce the depression and improve the quality of life of patients post-stroke significantly.Keywords: Medical Ministry Logotherapy, HDRS, WHOQOL, DPS